Comparative Analysis of Financial Performance Before and After IPO Case Study of PT. TBS Energi Utama TBK - MUNAWARAH, Munawarah; LAHAMIDO, Aprilian; PUTRA, I Nengah Oka Smara; RIZKY, Putri Dea (PT Keberlanjutan Strategis Indonesia, 2024)
This study aims to analyze the comparative financial performance of PT TBS Energi. The financial performance is analyzed using financial statement data from 2019 to 2023, which includes key indicators such as revenue and net profit, as well as financial ratios, including profitability, liquidity, and solvency ratios. The main focus on liquidity ratios includes the Current Ratio and Quick Ratio, which indicate the company's ability to meet short-term obligations. The entire financial statements of PT TBS Energi Utama Tbk published during the period under study were used as the subject of this research. The analysis results show that after the IPO, PT TBS Energi Utama Tbk experienced a significant increase in revenue and net profit, with consistent annual growth. Profitability ratios, including gross profit margin and net profit, also showed positive improvements. In addition, liquidity ratios, both Current Ratio and Quick Ratio, improved significantly, indicating that the company is better able to meet its short-term obligations after securing funds from the IPO.